Penyelesaian Wanprestasi Simpanan Deposito Akad Mudharabah yang Tidak Dikembalikan oleh Pihak KSU Syariah BMT Berlian: (Studi Putusan Nomor 37/Pdt.G/2018/PN Bau) - Zenita Putri, Fiska; Wardani, Susilo (Universitas Serang Raya, 2023)
Default is an act of violation of an agreement between two parties. When one party is unable to carry out its obligations in accordance with the existing agreement, then this action can be fully said to be a default. Mudharabah deposits are deposits of funds with a scheme where the owner of the funds (shahibul maal) entrusts his funds to be managed by the bank (mudharib) with the results obtained shared between the owner of the funds and the bank with the ratio agreed upon from the start. This research aims to analyze the factors that cause default of unreturned mudharabah contract deposits in Decision Number 37/Pdt.G/2018/PN Bau and to analyze the settlement of default of unreturned mudharabah contract deposits in Decision Number 37/Pdt.G/2018/PN Bau. The focus of this research covers the settlement of default of mudhrabah contract deposits that are not returned by the bank. This research uses a qualitative normative juridical method through a statutory approach using secondary legal data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research, it can be concluded that the factors causing default of mudharabah contract customer deposits that are not returned by KSU Syariah BMT Berlian, namely the first cause of default is the negligence of one of the parties. Second, the parties deliberately violated the contract agreement and violated Article 36 of the Compilation of Sharia Economic Law. The settlement of the default case of mudharabah contract deposits that were not returned by the KSU Syariah BMT Berlian was that the Panel of Judges had decided the case in accordance with statutory regulations, namely Article 1246 of the Civil Code and also contained in Article 38 of the Compilation of Sharia Economic Law.